2004
DOI: 10.1002/biof.552210161
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and hypoglycemic effect of ferulic acid in STZ‐induced diabetic mice and KK‐Ay mice

Abstract: Antioxidant activity and biological properties of ferulic acid (FA) are well recognized. This study was designed to estimate the potential utility of FA administered orally at low dosage for improvement of hyperglycemia in diabetes. With this aim we have evaluated the hypoglycemic effect of FA in two type diabetic animal models: (1) streptozotocin (STZ)-induced diabetic mice, a model of insulin-dependent diabetes mellitus (IDDM); (2) KK-Ay mice, a model of non-insulin dependent diabetes mellitus (NIDDM). In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
107
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 12 publications
2
107
0
1
Order By: Relevance
“…(Ligusticum) (8). FA exerts multiple biological activities such as antioxidant, and anti-inflammation (9,10) and it is known for treatment of Alzheimer's disease (11), cardiovascular disease (12), and cancer (13). In addition, FA is reported to have hepato-protective activity (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…(Ligusticum) (8). FA exerts multiple biological activities such as antioxidant, and anti-inflammation (9,10) and it is known for treatment of Alzheimer's disease (11), cardiovascular disease (12), and cancer (13). In addition, FA is reported to have hepato-protective activity (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the activity of these compounds helps increase the insulin level in the blood. Several studies have reported that treatment with ferulic acid or p-coumaric acid showed effective hypoglycemic activity in diabetic mice and that derivative compounds stimulated insulin secretion (33)(34)(35). Furthermore, the hydroxycinnamic acids have been utilized as potent UV-radiation absorbent compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that FA is an antioxidant that neutralizes free radicals such as superoxide, nitric oxide and hydroxyl radicals that may cause oxidative damage to cell membranes and DNA (Kanski et al, 2002;Ha et al, 2008). FA provides meaningful synergistic protection against oxidative stress in the skin and should protect against photoaging and skin cancer (Lin et al, 2005), hypoglycemic and hypolipidemic effects (Sri Balasubashini et al, 2003;Ohnishi et al, 2004;Jung et al, 2007), hypotensive effects (Suzuki et al, 2002), and anti-inflammatory effects (Yagi and Ohishi, 1979).…”
Section: Introductionmentioning
confidence: 99%